2015
DOI: 10.3354/esr00663
|View full text |Cite
|
Sign up to set email alerts
|

Umbrella species in marine systems: using the endangered humphead wrasse to conserve coral reefs

Abstract: Extinction risk is closely tied to body size, home range, and species distribution. Quantifying home range is critical for conservation, and can enable the use of concepts such as 'umbrella species', whose conservation protects other species due to shared habitat. To determine the value of the humphead wrasse as an umbrella species for coral reef conservation, we conducted a multi-year study of humphead wrasse home range at Palmyra Atoll, Central Tropical Pacific, tagging juvenile, female, and male individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 79 publications
2
18
1
Order By: Relevance
“…Of particular interest were individual-level variations in movement patterns, which leads to further questions regarding how the regional population uses this habitat and the ecological mechanisms underlying different behaviors. This evidence adds to that found in other sites within the Caribbean (Moncada et al 2012, Revuelta et al 2015, suggesting that locally increased marine protection in the area might positively impact this species and also lead to hawksbills being used as an alternate umbrella species for coral reefs (Weng et al 2015).…”
Section: Patterns Of Movementsupporting
confidence: 61%
“…Of particular interest were individual-level variations in movement patterns, which leads to further questions regarding how the regional population uses this habitat and the ecological mechanisms underlying different behaviors. This evidence adds to that found in other sites within the Caribbean (Moncada et al 2012, Revuelta et al 2015, suggesting that locally increased marine protection in the area might positively impact this species and also lead to hawksbills being used as an alternate umbrella species for coral reefs (Weng et al 2015).…”
Section: Patterns Of Movementsupporting
confidence: 61%
“…The incision was closed with a single suture and the shark was released. Shark movements were tracked by a network of over 70 underwater listening stations (VR2Ws) that were strategically positioned within all habitat types around the atoll and downloaded annually (for details see Papastamatiou et al 2015, Weng et al 2015. The complete set of receivers were only in place from 2010, so we analyzed data from blacktip reef sharks tagged prior to 2010 separately.…”
Section: Movements and Habitat Usementioning
confidence: 99%
“…We maintain a large array of Vemco VR2W receivers at Palmyra Atoll (Weng et al 2015). We increased the receiver array (from that shown in Weng et al 2015) at the Western Terrace with 5 receivers placed 100 m apart in 2013 ( Fig.…”
Section: Passive Acoustic Monitoringmentioning
confidence: 99%
“…We maintain a large array of Vemco VR2W receivers at Palmyra Atoll (Weng et al 2015). We increased the receiver array (from that shown in Weng et al 2015) at the Western Terrace with 5 receivers placed 100 m apart in 2013 ( Fig. 1C), basing spacing of the receivers on reported receiver detection ranges in shallow coral reef habitat (Welsh et al 2012) and reported extents of movement for this species (Welsh & Bellwood 2012b).…”
Section: Passive Acoustic Monitoringmentioning
confidence: 99%